2011
DOI: 10.1074/jbc.m111.253385
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-CoA:Lysophosphatidylcholine Acyltransferase I (Lpcat1) Catalyzes Histone Protein O-Palmitoylation to Regulate mRNA Synthesis

Abstract: The enzyme acyl-CoA:lysophosphatidylcholine acyltransferase (Lpcat1) is a critical cytosolic enzyme needed for lung surfactant synthesis that catalyzes an acyltransferase reaction by adding a palmitate to the sn-2 position of lysophospholipids. Here we report that histone H4 protein is subject to palmitoylation catalyzed by Lpcat1 in a calcium-regulated manner. The enzyme acyl-CoA:lysophosphatidylcholine acyltransferase (Lpcat1) was recently cloned from lung epithelia and is indispensable for generation of pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 28 publications
(13 reference statements)
1
79
1
Order By: Relevance
“…In a recent study it has been demonstrated that lipopolysaccharide causes polyubiquitination and subsequent degradation of acyl-CoA:lysophosphatidylcholine acyltransferase, an enzyme critically involved in the synthesis of the bioactive surfactant phospholipid, dipalmitoylphosphatidylcholine, using the Skp1-Cullin-F-box ubiquitin E3 ligase component, b -transducin repeat-containing protein. 33 Furthermore, in a murine model of Pseudomonas aeruginosa -induced surfactant deficiency, which was characterized by the loss of CTP: phosphocholine cytidylyltransferase a , a nuclear enzyme that catalyzes the rate-limiting step in phosphatidylcholine synthesis, lung injury could be prevented by inhibition of the Skp1-Cullin-F-box E3 ligase, which was shown to monoubiquitinate CTP:phosphocholine cytidylyltransferase a leading to its degradation. Thus, ubiquitination may be critically important in surfactant homeostasis and ALI.…”
Section: Role Of Ubiquitination In Acute Lung Infl Ammation and Surfamentioning
confidence: 99%
“…In a recent study it has been demonstrated that lipopolysaccharide causes polyubiquitination and subsequent degradation of acyl-CoA:lysophosphatidylcholine acyltransferase, an enzyme critically involved in the synthesis of the bioactive surfactant phospholipid, dipalmitoylphosphatidylcholine, using the Skp1-Cullin-F-box ubiquitin E3 ligase component, b -transducin repeat-containing protein. 33 Furthermore, in a murine model of Pseudomonas aeruginosa -induced surfactant deficiency, which was characterized by the loss of CTP: phosphocholine cytidylyltransferase a , a nuclear enzyme that catalyzes the rate-limiting step in phosphatidylcholine synthesis, lung injury could be prevented by inhibition of the Skp1-Cullin-F-box E3 ligase, which was shown to monoubiquitinate CTP:phosphocholine cytidylyltransferase a leading to its degradation. Thus, ubiquitination may be critically important in surfactant homeostasis and ALI.…”
Section: Role Of Ubiquitination In Acute Lung Infl Ammation and Surfamentioning
confidence: 99%
“…Fluorescent immunostaining was conducted as previously described (Zou et al, 2011b). Briefly, cells (2×10 5 ) were plated at 70% confluence onto 35-mm MatTek glass-bottomed culture dishes.…”
Section: Immunostainingmentioning
confidence: 99%
“…Murine lung epithelial (MLE) cells were cultured in HITES medium (500 ml of DMEM/F12, 2.5 mg of insulin, transferrin, sodium selenite, 2.5 mg of transferrin, 10 μM hydrocortisone, 10 μM β-estradiol, 10 mM Hepes, and 2 mM L-glutamine) and supplemented with 10% fetal bovine serum, as described previously (Zou et al, 2011b). MG132 (20 µM final concentration), leupeptin (20 µM final) and cycloheximide (10 µM) were purchased from Calbiochem.…”
Section: Cell Line and Reagentsmentioning
confidence: 99%
“…Interestingly, LPS treatment and bacterial infection triggers Lpcat1 to migrate into the nucleus. Nuclear Lpcat1 catalyzes a novel histone modification referred to as histone O-palmitoylation that regulates pro-inflammatory gene transcription [6,15]. LPS treatment also results in Histone acetyltransferases binding to origin recognition complex (HBO1) degradation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these chemical groups are well studied small chemicals that include the acetyl, methyl, or phosphorus groups. Some of them are small proteins such as ubiquitin, or even long chain fatty acid palmitoyl group [6].…”
Section: Introductionmentioning
confidence: 99%